Bulgaria Through the Eyes of Marijan Alkovic and Franjo Horvat Kis - Antoaneta Balcheva (Zeszyty Cyrylo-Metodiańskie)
The article discusses the impressions of Marijan Alkovic (1879–1953) and Franjo Horvat-Kis (1876–1924) from their visit to Bulgaria on the eve of the First World War, against the background of the dynamic change in the social, psychological and political attitudes of both the individual and various national communities. Their travelogues, both published in 1911, are interpreted as constructing a complex labyrinth of dialogues with otherness. The authors place their observations in the context of different cultural-historical, socio-political, religious and ethnic societal patterns. Such impressions, together with the Slavophile pathos, also reveal an updated author’s narrative of the era, the cartography of the Croatian, Bulgarian and South Slavic space. A special emphasis is placed on the figure of the traveler, who has gained an ever greater complexity, combining the roles of the writer, publicist, researcher and politician. Original title in Bulgarian: България през очите на Мариян Алкович и Франьо Хорват Киш.